The Unexamined Relationship Between Neoliberalism and Plurilingualism: A Cautionary Tale. Issue 3 (16th August 2013) - Flores, Nelson
<x xml:space="preserve">Abstract</x> In recent years, TESOL scholars have offered both explicit and implicit critiques of language ideologies developed within nationalist frameworks that positioned monolingualism in a standardized national language as the desired outcome for all citizens. These scholars have used insights from both the social and the natural sciences to call into question static conceptualizations of language and have reconceptualized language pedagogy in ways that place the fluid and dynamic language practices of bilingual students at the center of instruction. This dynamic turn in TESOL has informed the emergence of plurilingualism as a policy ideal among language education scholars in the European Union. This article argues that this shift in the field of TESOL parallels the characteristics of the ideal neoliberal subject that fits the political and economic context of the current sociohistorical period—in particular, the desire for flexible workers and lifelong learners to perform service‐oriented and technological jobs as part of a post‐Fordist political economy. These parallels indicate a need for a more critical treatment of the concept of plurilingualism to avoid complicity with the promotion of a covert neoliberal agenda. The article ends with a framework for TESOL that works against the grain of neoliberal governance.